2003
DOI: 10.1144/0016-764901-087
|View full text |Cite
|
Sign up to set email alerts
|

U–Pb geochronology of deformed metagranites in central Sutherland, Scotland: evidence for widespread late Silurian metamorphism and ductile deformation of the Moine Supergroup during the Caledonian orogeny

Abstract: Within the Caledonides of central Sutherland, Scotland, the Neoproterozoic metasedimentary rocks of the Moine Supergroup record NW-directed D 2 ductile thrusting and nappe assembly, accompanied by widespread tight-to-isoclinal folding and amphibolite-facies metamorphism. A series of metagranite sheets which were emplaced and penetratively deformed during D 2 have been dated using SHRIMP U-Pb geochronology. Zircon ages of 424 AE 8 Ma (Vagastie Bridge granite), 420 AE 6 Ma (Klibreck granite) and 429 AE 11 Ma (St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 58 publications
3
99
0
1
Order By: Relevance
“…Within various sectors of the North Atlantic Caledonides it has therefore been possible to differentiate deformation fabrics and mineral assemblages formed during early phases of Ordovician arc-continent collision from those formed during Silurian continental collision (e.g. Kinny et al 1999Kinny et al , 2003Roberts 2003;Kocks et al 2006;Bird et al 2013).…”
mentioning
confidence: 99%
“…Within various sectors of the North Atlantic Caledonides it has therefore been possible to differentiate deformation fabrics and mineral assemblages formed during early phases of Ordovician arc-continent collision from those formed during Silurian continental collision (e.g. Kinny et al 1999Kinny et al , 2003Roberts 2003;Kocks et al 2006;Bird et al 2013).…”
mentioning
confidence: 99%
“…In north Sutherland, Holdsworth (1989) and Holdsworth et al (2001) SSE to south plunging lineations (suggesting NNW to northerly directed transport) for high-level thrusts, such as the Sgurr Beag and Naver thrusts, as well as in nearby syn-tectonic intrusions, are widely reported along the length of the Northern Highlands (Rathbone & Harris 1979;Kelley & Powell 1985;Grant & Harris 2000;Kinny et al 2003a). This would suggest that the early ductile Sgurr Beag-type thrusts did have a systematically different transport direction to the lower, Moine Thrust.…”
Section: Lineations and Transport Directionmentioning
confidence: 98%
“…The main phase of ductile thrusting and associated folding and fabric development affecting the Morar Group probably occurred slightly earlier, in the interval 435 -430 Ma (Kinny et al 2003a;Goodenough et al in review). This would imply that all deformation episodes from D2 Ac onwards (Fig.…”
Section: Timing Of Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent radiometric studies have confirmed the existence of Neoproterozoic (800-750 Ma) tectonothermal events within both the Moine and the oldest rocks of the Northern Grampian Highlands (Noble et al, 1996;Highton et al, 1999), yet in the higher Grampian, Appin and Argyll group rocks of the Dalradian succession, only Palaeozoic (470-450 Ma) Caledonian events are known (e.g. Rogers andPankhurst, 1993, Smith et al, 1999). Comparable dating studies now recognize discrete tectonothermal events and it remains one of the key issues of Highland geology to define the limits of these events.…”
Section: Introductionmentioning
confidence: 97%